Pulmonary hydatid echinococcosis in the child: Consideraciones generales: Sintomatología, complicaciones - Benedictti, Juan Luis; Amoza, Benito; Bentancur, Bernabé (Cirugía del Uruguay, 1984)
General considerations are made in respect of its frequency, and also its number and situation in the lung. Predominantly in children aged between 4 and 10. lt may appear through a proteiform symptomatology. X-Ray examination is of fundamental importance. Anatomic and physiologicai condition of the lung fa• vour a higher frequency of complications. Lung Hydatid Echinococcosis must have early diagnosis, based on X-Ray examination and immunobiological reactions and clinical background.